2018
DOI: 10.20319/pijtel.2018.22.5165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gamification on Khan Academy in Brazilian High School

Abstract: This article approaches current pedagogical practices in the national guidelines, related to the use of information and communication technologies. We report the actions taken in a compulsory curricular internship of the bachelor's degree in informatics of the UTFPR-Francisco Beltrão Campus. The internship student performs observation and experiment inside a first-year high school classroom and suggest the use of an e-learning tool to support learning,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Teaching basic numeracy to children who have a deficit in communication, such as those with ASD, is more possible when the content is gamified using multimedia technologies [ 16 ]. All participants in this study used games when teaching various subjects in class.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching basic numeracy to children who have a deficit in communication, such as those with ASD, is more possible when the content is gamified using multimedia technologies [ 16 ]. All participants in this study used games when teaching various subjects in class.…”
Section: Discussionmentioning
confidence: 99%
“…Educational websites such as IXL Worldwide [ 12 ] and Khan Academy [ 15 ] provide content to support the learning of children with learning disabilities, including dyslexia, dysgraphia, attention deficit and hyperactivity disorder, and visual-motor deficit. The introduction of gamification in Khan Academy videos has proved promising to bring new ways of engaging students with activities and providing valuable data for teachers [ 15 , 16 ]. Moreover, several studies [ 17 - 19 ] have shown that online content for teaching mathematics positively impacted a variety of learning environments.…”
Section: Introductionmentioning
confidence: 99%
“…Once students finish watching a video or article, it will add corresponding points while jumping on to the next section (either answering a question or another video to watch). Therefore through gamification, students can fill a sense of satisfaction after watching those videos and receiving those points, thus likely to get motivated to learn more [7].…”
Section: Gamificationmentioning
confidence: 99%
“…Gamification can be in various forms, as stated in the definition, forms such as badges, points, and leaderboards motivate students to dig into the learning process [4,9]. According to the studies, badges were most useful for motivating students, which resulted in significant improvement [7,10]. However, due to forms such as leaderboards, students are more likely to compete with each other.…”
Section: Gamification As the Motivation For Academicmentioning
confidence: 99%
“…Andere Lernplattformen sind mit spezifischeren pädagogischen Lernzielen konzipiert. Eine dieser Plattformen ist Khan Academy, welche mit Prinzipien des Adaptiven Lernens mit Gamification-Elementen arbeitet, um Lernenden zu unterstützen und zu motivieren (Klock et al, 2015;Tenório et al 2018). (Merkt et al, 2011).…”
Section: Dennoch Sind Häufig Verwendete Plattformen Wie Moodle Eher Für Die Verwaltung Vonunclassified